Voluntary Participation: Situation and Perspectives in Lithuania after 1990’s - Butkuvienė, Ernesta (Sociologija. Mintis ir veiksmas, 2005)
The article is aimed at discussing the major presumptions and tendencies of civil participation in voluntary activities in Lithuania after 1990. Despite the objective conditions for public activism in social and political life, participation in non-governmental sector is still low in Lithuania, as only near 13% of the population take part in the activities of NGOs. Following social capital, social exchange theories, civil participation in voluntary activities is one of the ways to influence social processes. According to the results of qualitative (semi-structured interviews with NGO members) and quantitative (national public opinion survey) research, more than a half of the Lithuanian population do participate in different activities on a grass-root level, including sports, tourists clubs, dwellers associations, committees at kinder-gartens and schools. However, participation in NGOs such as: organizations of human rights, animal care, environmental organizations, support funds, etc. is extremely low. Economic and social problems, including low living standards, high rate of unemployment and poverty, as well as scarce traditions of philanthropy partially explain passive civil participation in voluntary activities. Taking into account the importance of civil engagement in NGOs for the community and the society, more information on the benefits of voluntarism, as well as examples of good practice is needed.